Green management: the reality of being green in business - Tran, Ben (2009)
Green management and going green are not as clear cut and easy as hyped by the general media. While going ecologically green is indeed beneficial and appropriate, the process and procedure of becoming green is anything but easy. Firstly, turning green is largely not a legal requirement, but a voluntary process. Thus, even though LEED (which is by far the more publicly known green certification standard) governs the certification of the green management effort, it is not a compulsory condition for practitioners to go green. Secondly, even with the encouragement of incentives to comply, practitioners are skeptical in becoming green due to: (a) a lack of true understanding of the benefit of ecologically friendly procedures (the practice of profits versus the theory of benefits); (b) lack of short term gain in life cycle costing (practitioners want instant incentives); and (c) mostly, because it is not a legal requirement for the vast majority of municipalities.